Avaliando a influência de indivíduos imunes na propagação de doenças contagiosas - Moraes, Ana Leda Silva (2016)
Epidemiology is the science that studies the occurrence of diseases in a population. The results of these studies allow a comprehension of a disease propagation and enable actions in order to control epidemics. There are many mathematical models used in epidemiological studies; in which SIR-like models are the most used. In this model, the population is divided into three groups: S - susceptible individuals to infection, I - infected individuals, and R - recovered individuals. The proposal of this thesis is, based on a new SIR model, taking into consideration the effect of recovered individuals on the propagation of contagious diseases and on the recovery of sick individuals. This can be relevant to the study of propagation of typical diseases in children, since immune individuals can catalyze the encounters among susceptible children and infected children, as well as to contribute to the recovery of sick individuals. The predictive ability of the proposed model is evaluated from the records refering to the incidence of chickenpox in Belgium, Germany and Italy, in a pre-vaccination era.